Mechanisms underlying presynaptic facilitatory effect of cyclothiazide at the calyx of Held of juvenile rats - Ishikawa, Taro (Blackwell Science Inc, 2001)
1. Excitatory postsynaptic currents (EPSCs) were recorded using the whole-cell patch-clamp technique at the calyx of Held synapse in the medial nucleus of the trapezoid body (MNTB) in auditory brainstem slices from juvenile rats. 2. Bath application of cyclothiazide (CTZ, 100 μm) significantly increased the amplitude of EPSCs mediated by α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) and N-methyl-d-aspartate (NMDA) receptors. Cyclothiazide increased the magnitude of paired-pulse depression of both AMPA-EPSCs (intervals, 50 and 500 ms) and NMDA-EPSCs (interval, 20 ms). In low Ca(2+), high Mg(2+) solution, CTZ decreased the number of failures and increased the mean amplitude of AMPA-EPSCs more than three-fold. 3. Presynaptic Ca(2+) currents and K(+) currents were directly recorded from the calyceal nerve terminals. These currents were attenuated by CTZ in a reversible manner. The magnitude of inhibition of presynaptic K(+) currents by CTZ (100 μm) was comparable to that by 5 μm 4-aminopyridine (4-AP). Both CTZ and 4-AP slowed the repolarizing phase of presynaptic action potentials. 4. The inhibitory effects of CTZ on presynaptic ion channels were mimicked by a solution having reduced Ca(2+) concentration and 5 μm 4-AP. This solution facilitated EPSCs, but the magnitude of facilitation was significantly less than that caused by CTZ. 5. In the presence of tetrodotoxin (TTX), CTZ increased the mean frequency of miniature EPSCs three-fold. CTZ prolonged their decay time but had no effect on their amplitude. The facilitatory effect of CTZ on the miniature frequency was neither blocked by a protein kinase C inhibitor nor occluded by phorbol ester, suggesting that a distinct mechanism underlies the effect of CTZ. 6. We conclude that CTZ facilitates transmitter release through suppression of presynaptic potassium conductance and stimulation of exocytotic machinery downstream of Ca(2+) influx.